Activity and phylogenetic diversity of sulfate-reducing microorganisms in low-temperature subsurface fluids within the upper oceanic crust - Robador, Alberto; Jungbluth, Sean P; LaRowe, Douglas E; Bowers, Robert M; Rappe, Michael S; Amend, Jan P; Cowen, James P (FRONTIERS IN MICROBIOLOGY, 2015)
The basaltic ocean crust is the largest aquifer system on Earth, yet the rates of biological activity in this environment are unknown. Low-temperature ({<}100 degrees C) fluid samples were investigated from two borehole observatories in the Juan de Fuca Ridge (JFR) flank, representing a range of upper oceanic basement thermal and geochemical properties. Microbial sulfate reduction rates (SRR) were measured in laboratory incubations with S-35-sulfate over a range of temperatures and the identity of the corresponding sulfate-reducing microorganisms (SRM) was studied by analyzing the sequence diversity of the functional marker dissimilatory (bi)sulfite reductase (dsrAB) gene. We found that microbial sulfate reduction was limited by the decreasing availability of organic electron donors in higher temperature, more altered fluids. Thermodynamic calculations indicate energetic constraints for metabolism, which together with relatively higher cell-specific SRR reveal increased maintenance requirements, consistent with novel species-level dsrAB phylotypes of thermophilic SRM. Our estimates suggest that microbially-mediated sulfate reduction may account for the removal of organic matter in fluids within the upper oceanic crust and underscore the potential quantitative impact of microbial processes in deep subsurface marine crustal fluids on marine and global biogeochemical carbon cycling.
Keywords: ROV Jason (Remotely Operated Vehicle)